Rancangan Bangun Otomasi Air Suling Daun Cengkeh Berbasis Arduino - Muhamad Khoirul Umam; Danang Danang; Eko Siswanto; Nuris Dwi Setiawan (Repeater : Publikasi Teknik Informatika dan Jaringan, 2024)
The MSME group "Manuggal Karya" located in Ngambarsari Village, Karang Tengah District, Wonogiri, Central Java is a business group that operates in the field of refining clove leaf essential oil. can be monitored properly so that overflowing essential oils often spill from the reservoir and improper handling can actually cause the essential oils to become dirty. The use of an automation system that can keep essential oils sterile and can stop the flow of oil to the reservoir if the reservoir is full. The result that the author hopes is that by making this tool, the MSME Group "Manunggal Karya" can increase production efficiency to produce quality clove leaf essential oil.